Investigations of the CN/Cu(1 1 1) system using density functional theory - Shuttleworth, I.G. (Surface science, 2008)
The geometry, CN–CN interaction and surface bond strength and structure of the CN–Cu(1 1 1) system has been investigated using LCAO-DFT. The lowest energy adsorption sites for perpendicularly oriented, C down CN has been shown to be threefold with a slight preference for the fcc site. The binding energies for the two and threefold sites have been shown to lie in the range 1.441–1.574 eV. Studies of the electron density contours have shown an enhancement of charge in the σ-bond and a depletion of charge in the π-bond for binding in the fcc, hcp and twofold sites. A similar charge distribution is seen for CN groups bound in tilted orientations though at lower binding energies. For both the perpendicular and tilted orientations the Cu atoms closest to the C atom are seen to undergo nominal out of plane displacements of −0.02 to 0.08 Ǻ accompanied by an internal repolarization of their charge. An estimate of the lateral interaction strength of between 8.3% and 9.6% of the CN-surface binding energy for each high symmetry binding position has been obtained for perpendicular bound CN. The estimated energy differences due to lateral effects estimated with DFT are energetically comparable to the reported energy differences between perpendicular and parallel adsorption structures for CN. Thus, very subtle effects that may be beyond the accuracy of DFT may determine the actual geometry in this system, which should not be addressed without also considering lateral interactions via unit cell size.